1963
DOI: 10.1126/science.140.3569.888
|View full text |Cite
|
Sign up to set email alerts
|

Timing Behavior in Rats with Water Drinking as a Mediator

Abstract: Rats, reinforced for spacing their responses 20 seconds apart, used water-drinking as a means of "pacing" their response rate. "Timing" may be based on mediating response sequences such as drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1

Year Published

1964
1964
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 6 publications
3
40
1
Order By: Relevance
“…Clark (1962) suggested that water drinking on a VI bar-pressing schedule is maintained adventitiously by the arrival of reinforcements soon after the subject shifts from drinking to bar pressing. A similar position was advanced by Segal & Holloway (1963), who concluded that collateral water drinking on a spacedresponse reinforcement schedule was part of a chain of behavior initiated by food and terminated by the next bar press. However, Segal & Deadwyler (1964b), on the basis of drinking data obtained while rats were under the effects of amphetamine, argued that the drinking is probably nothing more than "prandial" drinking prompted by thirst sensations produced by eating dry food, and is not adventitiously maintained by reinforcement contingencies.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Clark (1962) suggested that water drinking on a VI bar-pressing schedule is maintained adventitiously by the arrival of reinforcements soon after the subject shifts from drinking to bar pressing. A similar position was advanced by Segal & Holloway (1963), who concluded that collateral water drinking on a spacedresponse reinforcement schedule was part of a chain of behavior initiated by food and terminated by the next bar press. However, Segal & Deadwyler (1964b), on the basis of drinking data obtained while rats were under the effects of amphetamine, argued that the drinking is probably nothing more than "prandial" drinking prompted by thirst sensations produced by eating dry food, and is not adventitiously maintained by reinforcement contingencies.…”
mentioning
confidence: 77%
“…Problem Several investigators have reported unusual frequ€mcies and quantities of water drinking by rats maintained on interval reinforcement schedules for food. VI (Clark, 1962;Falk, 1961Falk, , 1964, DRL (Segal & Holloway, 1963; Segal & Deadwyler, 1964b) and freereinforcement (Segal & Deadwyler, 1964a) schedules produce the polydipsia, liquid as well as dry food reinforcers are effective (Falk, 1964), and alcohol solutions (Lester, 1961) as well as water are drunk. The aims of the present experiments were (1) to follow the time course of the development of polydipsia over days, and (2) to observe the interaction of water drinking and bar pressing, where neither was related to the delivery of reinforcements.…”
Section: Introductionmentioning
confidence: 99%
“…The present study suggests that once the mediating behavior is initiated by stimulus change it is no longer under stimulus control, but may be maintained until terminated by reinforcement. That mediating behavior is important in establishing accurate DRL performance has already been shown by Segal & Holloway (1963). Delayed reinforcement is probably effective in establishing DRL performance because it is the chain "bar press-mediating behavior" which is reinforced .…”
Section: Dlseusslonmentioning
confidence: 78%
“…(The recording pen reset to baseline following the completion of each 550 licks.) Performances typical of DRL schedules for other operants (Segal & Holloway, 1963) alternated with performances typical 272 of prandial drinking. The control of the experimental reinforcement schedule appears in the periods of lowrate licking, and the control of the thirst stimulus in periods of high-rate licking.…”
Section: Methodsmentioning
confidence: 97%